Examining Views of Science Teacher Candidates about E-Books - ÖCAL, Zekiye Merve; YÜZÜAK, Ahmet Volkan (Jurnal Penelitian dan Pembelajaran IPA, 2024)
This research aimed to investigate and obtain the opinions of science teacher candidates about e-books. The study was designed following the phenomenology research model which is one of the techniques of qualitative research. The research was carried out with 11 science teacher candidates. Every participant in the research was given access to a course that involved creating an electronic book with topic modules, relevant posters, and videos. This e-book was created with the assistance of the Exe-Learning software program. With the help of this program, users may produce their own books, movies, tests, and other e-learning resources. After learning how to use the application, participants selected the subjects and began to develop their own teaching-learning environment. Within the context of this study, science teacher candidates' comments about the e-book were gathered using a semi-structured interview form created by the researchers. Within the framework of this study, teacher candidates have constructed the e-book material sources. However, by building an e-book around the integration of creativity and self-regulation skills, in-service teachers may also create their own digital e-books with additional resources that effectively increase their students' creativity and self-regulation skills.